The distinct role of IL-34 and IL-35 in gastric cancer - He, Zhiyun; Dang, Jie; Cui, Xiang; Li, Bo; Bao, Shisan; Fan, Jingchun (Frontiers in Immunology, 2025)
Gastric cancer (GC) remains a major challenge due to its high mortality and morbidity, despite extensive research. Dysregulated host immunity plays a critical role in carcinogenesis, particularly among susceptible cohorts. In the gastric mucosa of GC patients, a reduction in IL-34 and TAM1, accompanied by an increase in TAM2 via M-CSF, enhances Th2 cell function, reduces pro-inflammatory activity, and elevates anti-inflammatory responses. Consequently, TAM2 acts in both paracrine and autocrine manners to polarize and boost TAM2, creating a tumour-favourable microenvironment that supports GC progression. High levels of TAM2, observed during advanced GC stages, suppress gastric IL-34 production, further promoting GC development. In contrast, IL-35, a cytokine involved in immune regulation and suppression, is produced by activated T cells and/or B cells in the affected gastric mucosa. Persistent H. pylori infection in GC tissues is associated with significant infiltration of IL-35-producing B cells and regulatory T cells (Tregs), which enhance the immunosuppressive and pro-tumour microenvironment by disrupting the local immune balance. Upregulated mucosal IL-35 promotes the polarization of TAM2 and Tregs while suppressing TAM1 cells, fostering a tumour-friendly environment that allows transformed gastric mucosal cells to evade immune surveillance, particularly in chronic H. pylori-infected patients. This cascade enhances proliferation and invasion while suppressing differentiation and apoptosis of GC cells. Together, the differential regulation of these cytokines creates an environment that supports cancer progression and resistance to therapy. Targeting the IL-34 and IL-35 pathways may offer a novel therapeutic strategy for improving outcomes in GC patients.